دور المواصفات القياسية في ضمان سلامة و جودة المواد الغذائية - دراسة في المواصفات التنظيمية الجزائرية - نوي, هناء (revue mofakir; No 13 (2016): مجلـــة المفكــر, 2018)
The health, safety and the quality of the alimentary materials is based specially nowadays on the Algerian consumer’s giving up gradually some bad habits and adopting the semi –manufactured foods are made according to some features and conditions called “ I deal features “ . These ideal features are a part of the Algerian consumer’s constitution, it conserves different process stages of putting the foods in the consumer’s hands and it’s all the same if alimentary materials is fresh, manufactured or semi-manufactured. But still providing, healthy, safe and secured and a good quality foods are related mainly to how firmly he haws and features are followed and worked with .